Characterization of the Immune Resistance of Severe Acute Respiratory Syndrome Coronavirus 2 Mu Variant and the Robust Immunity Induced by Mu Infection . (18th February 2022) - Uriu, Keiya; Cárdenas, Paúl; Muñoz, Erika; Barragan, Veronica; Kosugi, Yusuke; Shirakawa, Kotaro; Takaori-Kondo, Akifumi; ,; Sato, Kei
Abstract: Background: We have recently revealed that the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Mu variant shows a pronounced resistance to antibodies elicited by natural SARS-CoV-2 infection and vaccination. Methods: However, it remains unclear which mutations determine the resistance of SARS-CoV-2 Mu to antiviral sera. In addition, it is unclear how SARS-CoV-2 Mu infection induces antiviral immunity. Results: In this study, we reveal that the 2 mutations in the SARS-CoV-2 Mu spike protein, YY144-145TSN and E484K, are responsible for the resistance to coronavirus disease 2019 convalescent sera during early 2020 and vaccine sera. Conclusions: It is notable that the convalescent sera of SARS-CoV-2 Mu-infected individuals are broadly antiviral against Mu as well as other SARS-CoV-2 variants of concern and interest. Abstract : Two mutations in the SARS-CoV-2 Mu variant spike, YY144-145TSN and E484K, are responsible for the pronounced resistance to COVID-19 convalescent and vaccine sera. The convalescent sera of SARS-CoV-2 Mu-infected individuals are broadly antiviral against Mu as well as other variants.